Fiber-optic pH detection in small volumes of biosamples - Kasik, I; Mrazek, J; Martan, T; Pospisilova, M; Podrazky, O; Matejec, V; Hoyerova, K; Kaminek, M (Analytical and bioanalytical chemistry, 2010)
Determining the pH values of microscopic plant samples may help to explain complex processes in plants, so it is an area of interest to botanists. Fiber-optic probes with small dimensions can be used for this purpose. This paper deals with the fiber-optic detection of the pH values of droplets of plant xylem exudate based on ratiometric fluorescence intensity measurements with an internal reference. For this purpose, novel V-taper sensing probes with a minimum diameter of around 8 μm were prepared that enable the delivery of fluorescence signal from the detection site on the taper tip to the detector. The taper tips were coated with pH-sensitive transducer (8-hydroxypyrene-1,3,6-trisulfonic acid trisodium salt; HPTS) and a reference [dichlorotris-(1,10-phenanthroline) ruthenium (II) hydrate (Ru-phen dichloride)] immobilized in a xerogel layer of propyltriethoxysilane and (3-glycidoxy)propyl trimethoxysilane. The prepared probes were sensitive to pH values mainly in the range from 6.0 to 9.0. In the pH range 6-9, the results were limited by measurement errors of about 0.2 pH units, and in the pH range 5-6 by measurement errors of about 0.5 pH units. Using the developed V-taper sensing probes, the pH values of in vivo and in vitro samples of small volumes (~6 μl) of exudate were measured. The results were validated by comparison with conventional electrochemical pH measurements.
Keywords: fluorescenční barviva; Fluorescence; koncentrace vodíkových iontů; biosenzitivní techniky; technologie optických vláken; Biosensing Techniques; Fiber Optic Technology; velikost buňky; xylém; Fluorescent Dyes; Hydrogen-Ion Concentration; Xylem; fluorescence; Cell Size